Letter to the editor regarding, “Exploring diagnostic frontiers in oral squamous cell carcinoma: A comprehensive review from immunohistochemistry to genomic profiling” - Naji Naseef Pathoor; Pitchaipillai Sankar Ganesh; Rajesh Kanna Gopal (Oral Oncology Reports)
The comprehensive analysis of diagnostic markers and methods in OSCC includes recommendations for enhancing the significance and utility of the work. It emphasizes the need for standardized diagnostic indicators that are effective across different labs and clinical settings. Key recommendations also highlight the importance of demonstrating successful validation across diverse cohorts and providing concrete examples of interdisciplinary collaboration. Additionally, it suggests addressing quality of life and patient-centric outcomes, integrating cutting-edge technologies like AI-assisted imaging, and linking advancements in diagnosis to improved patient outcomes. The aim of these enhancements is to increase the article's value as a resource for scholars and medical professionals, ultimately leading to better patient care and outcomes in OSCC.